The potential key genes within focal adhesion that regulate mesenchymal stem cells osteogenesis or adipogenesis in microgravity related disuse osteoporosis: an integrated analysis - Zhao, Haoyang; Tu, Xiaolin (Frontiers in Endocrinology, 2025)
This study aimed to identify key genes related to focal adhesions (FA) and cells involved in osteoblast (OS) and adipocyte (AD) differentiation in osteoporosis. A mouse model of disuse osteoporosis was made by hindlimbs unloading (HLU)/Tail - suspension. Micro - CT and histological analysis were done, and differentially expressed genes (DEGs) from GSE100930 were analyzed. Soft clustering on GSE80614 OS/AD samples found FA - related candidate genes. protein-protein interaction (PPI) network and cytoHubba’s Degree algorithm identified key FA - genes, validated by quantitative polymerase chain reaction (qPCR). Key OS/AD - associated cells were identified by single - cell analysis. The mouse model showed decreased bone density, microstructure damage, increased marrow adiposity, and altered gene expression. Key FA - related genes for osteogenesis (ITGB3, LAMC1, COL6A3, ITGA8, PDGFRB) and adipogenesis (ITGB3, ITGA4, LAMB1, ITGA8, LAMA4) were found and validated. Key cells (chondrocyte, adipocyte, and osteoblast progenitors) are involved in specific pathways, with osteoblast progenitors having stronger interactions. Pseudotime analysis implies differentiation from chondrocyte progenitors to adipocyte, then osteoblast progenitors. This study provides new insights for disuse osteoporosis research.